2019
DOI: 10.1002/celc.201900966
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Quasi‐Solid‐State Bifunctional Device with Zinc‐Ion Microbattery and Photodetector

Abstract: The development of flexible and wearable electronics has raised the demand for their power sources, which will be not only adequately compact, but also integrated on one flexible substrate. Therefore, microscale batteries with high flexibility and performance are desired to meet the requirement for miniaturizing energy storage devices and integrating them with other flexible electronics together. Here, a flexible quasi‐solid‐state bifunctional system with zinc‐ion microbattery and photodetector was designed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…When the temperature changes to 60, −20, and −40 °C, our battery can deliver 113%, 91.9%, and 72.9% on average of the energy density at 20 °C, respectively. Notably, the performance of our battery at −40 °C surpasses that of a previously reported Li thin‐film battery (7.9 mWh cm –3 at 1.5 mW cm –3 ) [ 37 ] and that of almost all AZIBs (probably evaluated at 20 or 25 °C), such as a MnO x @Ti 3 C 2 T x AZIB (22 mWh cm –3 at 25 mW cm –3 ), [ 38 ] a polyaniline AZIB (49.2 mWh cm –3 at 140 mW cm –3 ), [ 39 ] a CNT/α‐MnO 2 AZIB (32.7 mWh cm –3 at 65.4 mW cm –3 ), [ 9c ] a δ‐MnO 2 AZIB (35.1 mWh cm –3 at 65.8 mW cm –3 ), [ 7a ] a MoO 3 AZIB (14.4 mWh cm –3 at 48 mW cm –3 ), [ 40 ] and a graphene/V 2 O 5 AZIB (21 mWh cm –3 at 526 mW cm –3 ). [ 2b ] The above results further corroborate the excellent electrochemical performance and environmental adaptability of our battery.…”
Section: Figurementioning
confidence: 99%
“…When the temperature changes to 60, −20, and −40 °C, our battery can deliver 113%, 91.9%, and 72.9% on average of the energy density at 20 °C, respectively. Notably, the performance of our battery at −40 °C surpasses that of a previously reported Li thin‐film battery (7.9 mWh cm –3 at 1.5 mW cm –3 ) [ 37 ] and that of almost all AZIBs (probably evaluated at 20 or 25 °C), such as a MnO x @Ti 3 C 2 T x AZIB (22 mWh cm –3 at 25 mW cm –3 ), [ 38 ] a polyaniline AZIB (49.2 mWh cm –3 at 140 mW cm –3 ), [ 39 ] a CNT/α‐MnO 2 AZIB (32.7 mWh cm –3 at 65.4 mW cm –3 ), [ 9c ] a δ‐MnO 2 AZIB (35.1 mWh cm –3 at 65.8 mW cm –3 ), [ 7a ] a MoO 3 AZIB (14.4 mWh cm –3 at 48 mW cm –3 ), [ 40 ] and a graphene/V 2 O 5 AZIB (21 mWh cm –3 at 526 mW cm –3 ). [ 2b ] The above results further corroborate the excellent electrochemical performance and environmental adaptability of our battery.…”
Section: Figurementioning
confidence: 99%
“…As summarized in Figure 5i, the developed ZIMB from the engraved soft template can deliver a maximum energy density of 322 μWh cm −2 and the power density of 710 μW cm −2 , manifesting the superior areal energy density and power density compared with other reported planar MESDs. [2,[23][24][25][37][38][39][40][41][42]…”
Section: Resultsmentioning
confidence: 99%
“…There have been numerous cathode materials reported, such as vanadium-based compounds, [19] manganese-based compounds, [22,26] Prussian blue analogs, [20] chevrel phase compounds, [27] and organic cathodes. [24,25] Among them, MnS, as a new type of Mnbased compounds, has rarely been reported in ZIMB applications. Previous studies have shown high specific capacity and low costs of the MnS for Zn ion battery applications, but met problems of poor cycling stabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with other energy storage systems, such as supercapacitors, Ni-MH, and LIBs as shown in Figure 2, the above merits, such as relatively higher energy density and power density, promote the upsurge of the research and application of ZIBs in flexible devices. 26,27,[38][39][40] Flexible ZIBs hold great potential for wearable applications taking advantages of their specific properties including superior flexibility, adaptability to deformation, and compatibility with the traditional textile industry as shown in Figure 1B. Currently, a series of flexible ZIBs with both energy storage performance and mechanical robustness have been reported.…”
mentioning
confidence: 99%